Decisão judicial democrática: o caminho entre o dever fundamental à fundamentação democrática e o direito fundamental à resposta constitucionalmente adequada ou hermeneuticamente desvelada - Boscatto, Muriele de Conto; Mosena, Maurício (Revista do Programa de Pós-Graduação em Direito, 2015)
This study reveals the concern with the theme of “democratic judi cial decision”, which presupposes the prior recognition, in attention to requi act the validity ments under the law of a democratic state, the fundamental duty to state reasons democratic and fundamental right to cons-titucionalmente appropriate response. The theory of fundamental rights gives the note of fundamentality to these fundamental duty and right, giving the normativity needed their applications. Already the Law Hermeneutics Review reveals how to implement and performs these duty and fundamental rights, which repre- sit face of the same coin, in overcoming voluntarism in the decision, pro prio the subject of subjectivism as subject the object - or to decide according to their conscience. The democratic reasoning leads to the proper constitutional-mind response.